Antibacterial Activity Of Sago Caterpillar Oil (Rhynchoporus bilineatus L.) From Minahasa Against Salmonella typhi and Staphylococcus aureus - Pua, Devis Christian; Mokosuli, Yermia Semuel; Sumampouw, Harry Maurits (Indonesian Biodiversity Journal, 2024)
Sago caterpillars are ethnomedically used as food and medicine by the people of several tribes in Indonesia. Sago caterpillar oil contains active compounds, especially fatty acids that have antibacterial potential. Research has been carried out which aims to obtain the bioactive content of sago worm oil and the antibacterial activity of Salmonella typhi and Staphylococcus aureus bacteria. Sago caterpillars are obtained from the Minahasa region. Four to six instar sago caterpillars are used for oil isolation. Analysis of the content of sago worm oil using the Gas Chromatography Mass Spectrophotometry method. Meanwhile, the antibacterial test used the agar diffusion method using pure cultures of Salmonella thypii and Staphylococcus aureus. The results showed that the average sago caterpillar oil was 0.26 to 0.28 ml per head. The results of the antibacterial test showed the highest inhibition of S. aureus at a concentration of 1000 mg/L, namely 8.04 mm, while the inhibition of growth of S. thypii was highest at a concentration of 1000 mg/L, namely 7.69 mm. Sago caterpillar oil has antibacterial potential.